PENGARUH PUPUK HAYATI TIENS GOLDEN HARVEST TERHADAP PERTUMBUHAN BIBIT KAKAO - Muhammad Hatta (Jurnal Floratek, 2010)
This study was aimed at determining effect of various concentrations of biological fertilizer Tiens Golden Harvest (TGH) on growth of cocoa seedlings. TGH fertilizer concentrations studied consisted of 4 levels, i.e. 0 mlL-1 water, 5 mlL-1 water, 10 mlL-1 water, and 15 mlL-1 water. The results showed that concentrations of TGH fertilizer significantly affected height of cocoa seedling at 30 and 60 day after planting (DAP), and stem diameter of cocoa seedling at 20, 30, 40, 50 and 60 DAP.  The best TGH fertilizer concentration was found at 15 mlL-1 water. However, TGH fertilizer concentration did not significantly affect height of cocoa seedling at age of 10, 20, 40 and 50 DAP, stem diameter at age of 10 DAP, leaf area, root length, wet and dry weight at 60 DAP.